Identification and cloning of the Neurospora crassa glyceraldehyde-3-phosphate dehydrogenase gene, gpd-1 - M. Sahni; J. A. Kinsey (Fungal Genetics Reports, 1997)
In work initially intended to use the am gene coding sequences as a reporter gene, 5’ RACE PCR (Frohman et al., 1988 Proc. Natl. Acad. Sci. USA. 85:8998-9002) with three gene specific nested primers was performed. The product was cloned and sequenced, but found not to represent the am gene. Comparison to sequences in Genbank revealed that the product could encode a product homologous to glyceraldehyde-3-phosphate dehydrogenase (GPD) from a variety of other organisms. Consequently the PCR product was used to screen a lambda gt-11 expression library (Sachs et al. 1986 J. Biol. Chem 261:869-873). The 1.3 kb insert from one cDNA clone was sequenced (Figure 1) and used to screen a Neurospora genomic library made in an EMBL-3 vector by E. Cambareri. All of the positive clones had a 7 kb BamHI fragment. Relevant portions of one of the genomic clones was sequenced (Figure 1) revealing two introns. Although the complete genomic clone was not sequenced, comparison of restriction fragments from the cDNA and genomic clones indicated that no other introns are present in the Neurospora gpd-1 gene.